1993
DOI: 10.1507/endocrj.40.715
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Receptor Expression in Follicular and Stromal Compartments of the Human Ovary over the Course of Follicular Growth, Regression and Atresia.

Abstract: Abstract. The cytologic localization and cellular levels of insulin receptors in the human ovary during follicular growth, regression and atresia were examined by the avidin/biotin immunoperoxidase techniques with a monoclonal antibody to insulin receptor. In primordial follicles, only the oocyte showed a weak immunostaining for insulin receptor, whereas the stromal cells surrounding primordial follicles were moderately immunostained. The earliest stage of follicular growth at which immunostaining for insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 29 publications
2
27
0
2
Order By: Relevance
“…Con- sequently, this suggests the intriguing possibility of myc expression involvement in the process of apoptosis during follicular atresia and/or the incorporation of surviving granulosa and theca cells from atretic follicles into the ovarian stroma to form interstitial tissue. Similar patterns of expression in the peripheral theca lutein cells of regressing corpora lutea and in the theca interna cells of atretic follicles as observed with myc oncoprotein have been shown with EGF receptor [16] and insulin receptor [27]. Immunohistochemical localization of myc oncoprotein in antral follicles.…”
supporting
confidence: 65%
“…Con- sequently, this suggests the intriguing possibility of myc expression involvement in the process of apoptosis during follicular atresia and/or the incorporation of surviving granulosa and theca cells from atretic follicles into the ovarian stroma to form interstitial tissue. Similar patterns of expression in the peripheral theca lutein cells of regressing corpora lutea and in the theca interna cells of atretic follicles as observed with myc oncoprotein have been shown with EGF receptor [16] and insulin receptor [27]. Immunohistochemical localization of myc oncoprotein in antral follicles.…”
supporting
confidence: 65%
“…They were localized in stroma and in oocytes, granulosa and thecal cells (interna and externa) of preantral, small antral and large follicles and in luteal cells. Similarly, insulin receptors or corresponding mRNAs have been reported in human ovary in stroma, granulosa and theca cells and oocytes of growing follicles (Poretsky et al 1985, El-Roeiy et al 1993, Samoto et al 1993, as well as in rat and human luteal cells (Ladenheim et al 1984, Samoto et al 1993. In pigs, the presence of insulin receptors has been previously investigated only in granulosa cells and their presence has been detected (Rein & Schomberg 1982, Otani et al 1985.…”
Section: Discussionmentioning
confidence: 87%
“…In our study, atretic follicles also presented a clear labelling in granulosa and thecal cells. In women, insulin receptor mRNAs have been detected in pycnotic granulosa cells (El-Roeiy et al 1993), whereas no immunoreactivity for insulin receptor has been revealed in atretic follicles (Samoto et al 1993). The presence of insulin receptor in granulosa and theca interna of atretic and healthy follicles, as well as in corpora lutea of both stages, may suggest that this receptor is constitutively expressed in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that high concentrations of IGF-I, as well as acting via specific IGF receptors, can also bind to insulin receptors within the follicle (Giudice 1992). Insulin receptors have been detected in oocytes, granulosa, and theca cells of human preantral follicles ( Samoto et al 1993), and also in bovine follicles (Armstrong et al 2001). Therefore, this would provide a further mechanism, in addition to lack of regulation by binding proteins, for over-stimulation of the oocyte in the presence of the highest concentration of recombinant IGF-I.…”
Section: Discussionmentioning
confidence: 99%